Literature Review: Hypogonadism in Men - Aulia, Aziza Chantiqka; Philip Habib (Jurnal Kesehatan dan Kedokteran, 2025)
Male hypogonadism is a medical condition characterized by reduced testosterone production due to disorders of the testes or the hypothalamic–pituitary axis. This study employs a quantitative approach to systematically review the literature on the prevalence, risk factors, and physiological and psychological impacts of hypogonadism in men. Data were drawn from clinical and observational studies published over the past four years that analyzed associations among testosterone levels, age, body mass index, and symptoms such as erectile dysfunction and decreased libido. The review indicates that hypogonadism is more common in men over 40 years of age, particularly those with obesity or metabolic disease. Beyond sexual function, the condition also affects muscle mass, bone density, and emotional balance. In conclusion, early detection and appropriate testosterone replacement therapy play an important role in improving quality of life and preventing long-term complications in men with hypogonadism.